Ezekiel Traditions in the Second Temple Period : 4QWords of Ezekiel in Its Broader Context - Hamernik, Anna Shirav (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This volume offers a fresh perspective on the composition 4QWords of Ezekiel found at Qumran, and the development and transmission of the textual traditions associated with the prophet Ezekiel during the Second Temple period. As the first comprehensive monograph on this composition, it explores the intricate relationship between WoEzek and the scriptural Book of Ezekiel. The study suggests that WoEzek, through its unique structural framework and selected oracles, reflects how Ezekiel's visions were interpreted during the Second Temple period. By placing WoEzek within its broader literary and historical context, the analysis challenges traditional views on this composition and highlights the significance of Ezekiel's prophecy in the evolution of apocalyptic literature. This resource is ideal for scholars and graduate students in Biblical Studies and Second Temple literature, especially those interested in the Dead Sea Scrolls and Ezekiel's prophetic writings.